Peningkatan Teknologi dalam Era Transhumanisme Menurut Perspektif Islam: Technological Enhancement in the Transhumanism Era From Islamic Perspective - Mohamad Baharudin , Lukman Hakim; Ahmad Yusoff , Atifah; Waipin, Noorafifah (Al-Basirah Journal, 2025)
Transhumanism, a movement that integrates advanced technologies such as genetic engineering, artificial intelligence, and neural implants, has been rapidly expanding in the current era of technological progress. This study examines how transhumanism, with its vision of biologically and mentally transforming and enhancing the human being, conflicts with Islamic principles that regard humans as the best creation of Allah (ahsan taqwim) and entirely dependent on Him in matters of life and death. The methodology used is qualitative analysis based on primary sources such as the Qur’an and hadith, as well as the views of Muslim scholars. The findings show that transhumanism challenges the Islamic concepts of tauhid and destiny, where attempts to improve human beings through technology can be seen as rejecting God’s decree. This study highlights the need for a more comprehensive Islamic theological framework to address these challenges and suggests that Muslims adopt more responsive forms of ijtihad towards technological developments while upholding the principles of aqidah and the objectives of the shariah (maqasid shariah) in navigating the transhumanist era.